Guiding principles for peptide nanotechnology through directed discovery. (11th May 2018) - Lampel, A.; Ulijn, R. V.; Tuttle, T.
Abstract : This review explores recent efforts in the experimental and computational mapping and searching of the peptide sequence space, or directed discovery, of functional peptide based nanoscale systems and materials. Abstract : Life's diverse molecular functions are largely based on only a small number of highly conserved building blocks – the twenty canonical amino acids. These building blocks are chemically simple, but when they are organized in three-dimensional structures of tremendous complexity, new properties emerge. This review explores recent efforts in the directed discovery of functional nanoscale systems and materials based on these same amino acids, but that are not guided by copying or editing biological systems. The review summarises insights obtained using three complementary approaches of searching the sequence space to explore sequence–structure relationships for assembly, reactivity and complexation, namely: (i) strategic editing of short peptide sequences; (ii) computational approaches to predicting and comparing assembly behaviours; (iii) dynamic peptide libraries that explore the free energy landscape. These approaches give rise to guiding principles on controlling order/disorder, complexation and reactivity by peptide sequence design.